Hubungan Ibu Hamil Perokok Pasif dengan Kejadian Ketuban Pecah Dini - Icha Dithyana; . Soetrisno; Ruben Dharmawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Premature Rupture of Membranes (PROM) is most important issues commonly encountered. Premature rupture of membranes can cause some complications for both mother and fetus and may increase maternal morbidity and mortality. The prevalence of smoking in Indonesia increase every year and 85.4% current smokers smoke in the home where their family members live with them, thus threatening the health and safety of the environment. This research aimed to analyze the correlation between pregnant passive smoker and premature rupture of membrane. Methode : This research is observational analytic research using case control approach. Total of 60 samples were selected with a fixed - disease sampling, are all expectant mothers and maternity patients at the RSUD Dr. Moewardi. Data were collected by interview and medical record. The data which is got then analyzed by the program Statistic Products and Service Solution (SPSS) for Windows Release 17.0 with the use of statistic test Chi Square. Result: There is a significant correlation between pregnant passive smoker and premature rupture of membrane where the results obtained by using statistical test Chi Square is p = 0.02 and OR= 3.5. Conclusion: Pregnant passive smoker is 3.5 times more risky for experiencing premature rupture of membrane than non-passive smoker. Keywords: Pregnant passive smoker, Premature Rupture of Membrane (PROM)